Existential Dissociation: to the Question of the Essence of Existential Consulting (eks-consalting). / Disociación existencial: a la cuestión de la esencia de la consultoría existencial (eks-consalting) - Gachegova, Irina O.; Verona, Sergei V. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT Familiar philosophy always offered in its "shop crutches" – something "kind a" for the mind and confidence that "everything is clear" and "life is never over." However, people disappointed in the consumer goods of existential recipes. Now, in connection with the rapid development of technical means through which "information about reality" spreads, "content", "texts" and "video", "comments on reality" and weekly "analytical reports on reality" are circulating: naivety: pleasures. Our task, the task of this text is try to feel, to see the "shifts" in reality and the means of its understanding, image, grasp, transformation.RESUMEN La filosofía familiar siempre se ofrecía en sus "muletas de taller", algo "bueno" para la mente y la confianza de que "todo está claro" y "la vida nunca termina". Sin embargo, la gente decepcionó en los bienes de consumo de recetas existenciales. Ahora, en relación con el rápido desarrollo de medios técnicos a través de los cuales se difunden "información sobre la realidad", "contenido", "textos" y "video", "comentarios sobre la realidad" y "informes semanales analíticos sobre la realidad" circulan: ingenuidad: placeres. Nuestra tarea, la tarea de este texto es tratar de sentir, ver los "cambios" en la realidad y los medios de su comprensión, imagen, comprensión, transformación